MODERN SYSTEM OF PREPARATION OF SPORTS RESERVE AND SELECTION OF GIFTED ATHLETES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Based on the above, the problem of choosing the volume, intensity, and direction of physical activity in accordance with the qualitative and quantitative changes occurring in a child's body at the initial stage of wrestling training requires serious analysis and reflection. Contrary to popular belief, the growth process is not continuous and balanced. Different parts of the body, organs, and systems develop unevenly.